Usefulness of lactate albumin ratio at admission to predict 28-day mortality in critically ill severely burned patients: A retrospective cohort study. Issue 8 (December 2022) - Dudoignon, Emmanuel; Quennesson, Thomas; De Tymowski, Christian; Moreno, Nabila; Coutrot, Maxime; Chaussard, Maïté; Guillemet, Lucie; Abid, Sonia; Fratani, Alexandre; Ressaire, Quentin; Cupaciu, Alexandru; Weinmann, Vagh; et al.
Highlights: Fluid resuscitation after burn injury is guided by biomarker. Lactate albumin ratio (LAR) at admission is an easy and reliable marker. In multivariate analysis accounting for ABSI, LAR levels at admission> 0.13 was independently associated with 28-day mortality (adjusted OR = 3.98 (IC95 1.88–8.35)). Prediction by LAR does not do better than lactate level alone. Abstract: Introduction: Lactate albumin ratio (LAR) has been used as a prognostic marker associated with organ failure in critically ill septic patients. LAR and its association with outcomes has never been studied in burned patients. The aim of this study was to evaluate the ability of LAR to predict 28-day mortality. Methods: A retrospective cohort study including all burn patients hospitalized in intensive care unit. The primary endpoint was the 28-day mortality. Results: One thousand three hundred thirty four patients were screened, and 471 were included between June 2012 and December 2018. Briefly, the population study was mainly composed by men (249, 59.1%), the median age, TBSA burned, full thickness, ABSI and IGS2 were 52 [34–68], 20 [10–40], 8 [1–23], 7 [5–9] and 25 [15–40] respectively. Fifty-two patients (12.4%) died at day 28 after admission. At admission, the LAR level was lower in 28-day survivors compared non-survivors (0.05 [0.04, 0.08] vs 0.12 [0.07, 0.26], p < 0.001 respectively). In multivariate analysis accounting for ABSI, LAR levels at admission> 0.13 was independently associated with 28-day mortality (adjusted OR = 3.98 (IC95 1.88–8.35)). The ability of LAR at admission to discriminate 28-day mortality showed an AUC identical when compared to SOFA and ABSI scores (0.81 (IC95 0.74–0.88), 0.80 (IC95 0.72–0.85) and (0.85 (IC95 0.80–0.90), p < 0.05, respectively). Patients with LAR levels ≥ 0.13 at admission had higher 28-day mortality (40.6% vs 6.8%, p < 0.001, HR 7.39 (IC95 4.28–12.76)). Conclusion: At admission, LAR is an easy and reliable marker independently associated to 28-day mortality in patients with severe burn injury, but prediction by LAR does not perform better than lactate level alone